2002
DOI: 10.1183/09031936.02.00225502
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble CD14 in bronchoalveolar lavage fluid of stable lung transplant recipients

Abstract: Macrophages, neutrophils and infection have been implicated in the genesis of the bronchiolitis obliterans syndrome (BOS) post lung transplantation. sCD14 is a soluble form of a shed-cell surface protein. It is capable of promoting cytokine-induced inflammation and it9s presence in clinically stable lung transplant recipients (LTR) might be important as an early marker of BOS.Bronchalveolar lavage (BAL) and blood samples were taken from 26 stable LTR, at or near their best forced expiratory volume in one secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
2
15
0
2
Order By: Relevance
“…Previous studies have shown the presence of LBP and sCD14 in the airways of healthy subjects [12,23]. Moreover, evidence indicates that LBP and sCD14 levels increase in patients with lung diseases [8,12,23] yet, to the best of the present authors' knowledge, the current study is the first showing elevated levels of both molecules in smokers.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Previous studies have shown the presence of LBP and sCD14 in the airways of healthy subjects [12,23]. Moreover, evidence indicates that LBP and sCD14 levels increase in patients with lung diseases [8,12,23] yet, to the best of the present authors' knowledge, the current study is the first showing elevated levels of both molecules in smokers.…”
Section: Discussionmentioning
confidence: 45%
“…Moreover, evidence indicates that LBP and sCD14 levels increase in patients with lung diseases [8,12,23] yet, to the best of the present authors' knowledge, the current study is the first showing elevated levels of both molecules in smokers. The fact that the levels of LBP and sCD14 were not significantly different between smokers and COPD patients suggests that both proteins might not play an important role in the development of COPD.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previous studies assessed pulmonary endothelial intercellular junction disruption [26] or loss of integrity of the proteoglycan components of the interstitial space [7] immediately after overflow, followed by rapid (12 h) endothelial cell remodeling and reestablishment of cell junction [27]. In our study, precapillary pulmonary hypertension correlated with interstitial edema at H48, indicating that delayed endothelium injury may be mainly caused by overflow.…”
Section: Discussionsupporting
confidence: 51%